2012
DOI: 10.2166/wh.2012.181
|View full text |Cite
|
Sign up to set email alerts
|

A post-implementation evaluation of ceramic water filters distributed to tsunami-affected communities in Sri Lanka

Abstract: Sri Lanka was devastated by the 2004 Indian Ocean tsunami. During recovery, the Red Cross distributed approximately 12,000 free ceramic water filters. This cross-sectional study was an independent post-implementation assessment of 452 households that received filters, to determine the proportion still using filters, household characteristics associated with use, and quality of household drinking water. The proportion of continued users was high (76%). The most common household water sources were taps or shallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…16 Another study conducted in Sri Lanka found that, 2 years after ceramic filters were distributed in response to the 2004 tsunami, 71% of households self-reported ceramic filter use that day or the day before. 17 Both studies, however, noted the importance and difficulty of establishing distribution mechanisms to provide or sell replacement parts to users.…”
Section: Introductionmentioning
confidence: 99%
“…16 Another study conducted in Sri Lanka found that, 2 years after ceramic filters were distributed in response to the 2004 tsunami, 71% of households self-reported ceramic filter use that day or the day before. 17 Both studies, however, noted the importance and difficulty of establishing distribution mechanisms to provide or sell replacement parts to users.…”
Section: Introductionmentioning
confidence: 99%
“…A cross‐sectional survey was administered by in‐person oral interview; methods have been described in detail (Casanova et al. 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional survey was administered by in-person oral interview; methods have been described in detail (Casanova et al 2012). Study protocols and materials were approved by the UNC Biomedical IRB (#09-1453) and the Ethical Review Committee of the Faculty of Medicine, University of Ruhuna, Sri Lanka.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations